Internationalization, competition and transfer of knowledge: And the efforts by companies in BRIC countries to enter markets in USA and Europe - Knut Ingar Westeren (European Regional Science Association (ERSA), 2013)
Internationalization and competition now cuts across national borders, a firm?s position in one country is no longer independent from its position in other countries. This has at least two implications, it is an advantage for the firm to be present in several major growth markets. It is also desirable integrate its activities on a worldwide scale, in order to exploit and coordinate linkages between these different locations. Two major structural changes we have seen in international trade occurring over the past 40 years is that companies now have far less risk to participate in international operations and transportation costs compared to the cost of the actual traded goods has dropped substantially. Competition now also cuts across sector boundaries and market segments: This growing complexity of competition has changed the determinants of firm organization and growth, as well as the determinants of location. No firm, not even a dominant market leader, can generate all the different capabilities internally that are necessary to cope with the requirements of global competition. Competitive success thus critically depends on a capacity to selectively source specialized capabilities outside the firm that can range from simple contract assembly to quite sophisticated design capabilities. This requires shift in organization, strategies and resources. Such changes in the organization of international production need further research on knowledge spillover through FDI and other critical aspects of the internationalization processes. In this paper we will use the Brazilian company JBS? acquisition of the US company Pilgrim?s Pride at the end of 2009 as an example to look further into the questions raised above. United States is the biggest poultry producer in the world, and has recently become exceptionally cost-competitive, pushing up the local industry?s global market share. Within a very short period of time JBS managed to integrate Pilgrim?s into its U.S. operations capturing substantial synergies in the process. As a result JBS increased its market share worldwide. However, this was only possible after a thorough restructuring, including changes in management, the centralization of corporate activities, the streamlining of sales channels, including international ones, and a considerable improvement in the product mix, with a higher ratio of value added-products.
Keywords: 330; Globalisation; Competition; Knowledge